Control of Dynamic Properties of InAs/InAlGaAs/InP Hybrid Quantum Well‐Quantum Dot Structures Designed as Active Parts of 1.55 μm Emitting Lasers. Issue 4 (13th November 2017) - Rudno‐Rudziński, Wojciech; Syperek, Marcin; Maryński, Aleksander; Andrzejewski, Janusz; Misiewicz, Jan; Bauer, Sven; Sichkovskyi, Vitalii I.; Reithmaier, Johann P.; Schowalter, Marco; Gerken, Beeke; Rosenauer, Andreas; Sęk, Grzegorz
Abstract : The molecular beam epitaxy grown structures are investigated, comprising of InGaAs quantum wells (QW) separated by a thin InGaAlAs barrier from InAs quantum dots (QDs), emitting at 1.55 μm, grown on an InP substrate. To control the coupling between QW and QD parts the thickness of the barrier is changed, which commands the wave function overlap. The tuning of that parameter allows for the study of the influence of the QW potential on the energy structure of states and their wave functions in QDs, changing from an uncoupled system, where the optical response is just a sum of responses from two isolated elements, to a strongly quantum mechanically coupled system, exhibiting mixed 2D‐0D characteristics. The changes of the energy structure that are deduced from the photoreflectance and photoluminescence spectroscopy results, supported by 8‐band k · p modeling, explain the measured differences in the photoluminescence decay times between samples with different barrier thicknesses. Abstract : Hybrid quantum well‐quantum dot structures offer improved characteristics for laser devices, especially increased modulation speed, crucial for telecom applications; however, their energy structure must be carefully designed. It is shown here that for the investigated InAs/InAlGaAs/InP system the lowest lying hole states are confined in quantum well layer, making the ground state transition indirect in real space, which increases the photoluminescence decay time.